MODERN MANAGEMENT ALGORITHMS FOR MENSTRUAL DYSFUNCTION IN ADOLESCENTS: FROM PATHOGENESIS TO EVIDENCE-BASED PRACTICE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Pubertal maturation of the hypothalamic–pituitary–ovarian axis is often accompanied by menstrual irregularities requiring careful differentiation between physiological and pathological conditions. This study evaluated diagnostic and treatment approaches in 120 adolescents with menstrual disorders. Abnormal uterine bleeding predominated (62%). Tranexamic acid was effective in 78% of cases, while combined oral contraceptives showed higher efficacy (92%) but more side effects. BMI significantly influenced risk, and dydrogesterone therapy achieved cycle stabilization in 84% of patients. A differentiated approach improves clinical outcomes.
Keywords: Adolescents, menstrual cycle disorders, abnormal uterine bleeding, dysmenorrhea, secondary amenorrhea, dydrogesterone, combined oral contraceptives, tranexamic acid, body mass index, HPO axis, evidence-based medicine.